A model for quantification of GDOES depth profiles. (March 2015) - Liu, Y.; Yu, W.H.; Wang, J.Y.
Abstract: The MRI (Mixing-Roughness-Information depth) model and the CRAS (Crater-Simulation) model are combined for the quantification of GDOES (glow discharge optical emission spectroscopy) depth profile by taking into account the effects of crater, roughness and preferential sputtering in depth profiling. This combined model is successfully applied for the quantification of the measured GDOES depth profiles of N in a nitride coating and of Ni in a Ni-coated copper substrate. Highlights: The MRI-CRAS model is developed for GDOES depth profile quantification. The roughness effect and the crater effect are quantitatively considered. The model is applied to quantify measured N-and Ni-depth profiles of coatings.